Aircraft NCAR C-130 Low-rate Data (netCDF) [NCAR/RAF] - NCAR/EOL Research Aviation Facility (Arctic Data Center)
Low-rate data in netCDF format are available here for each flight of the NCAR C-130 that occurred during the SHEBA project (16 flights total) in the spring and summer of 1998. The SHEBA C-130 dataset documentation (most of the materials made available in the previously-released data notebooks) have been put on-line via the RAF web site. This will enable all users of the data to access the most critical documentation and data quality materials and to assemble their own copies of the documentation package. This documentation web site may be reached by selecting the associated dataset SHEBA: Aircraft NCAR C-130 Documentation and Data Quality Materials.